Networks in office automation : - IFIP TC 6 International In-Depth Symposium on Networks in Office Automation (1984 : Sofia, Bulgaria); Boyanov, Kiril; International Federation for Information Processing. Technical Committee 6 (Amsterdam : North-Holland, 1985)
Includes bibliographies and index.